The link allocation problem on ATM-based personal communication networks - Lee, Teck Seng. (2008)
The field of wireless/mobile communication is at an interesting juncture in its development. The phenomenal worldwide growth of cellular telephony clearly demonstrates the fact that users place significant value on portability as a service feature. As end-user applications migrate towards Internet/WWW and broadband multimedia, it would be reasonable to expect strong consumer demand for wireless extensions to such services. The wireless personal communication networks (PCN) will play an important role throughout the 1990s and into the next century. Owing to the demand of a wireless service to integrated services such as data, voice, images and video, a high-speed backbone network to connect base stations in the microcells is required. One of the possible solutions is to use an ATM-based backbone network. In such an ATM-based PCN network, the communication path between a pair of mobile terminals might be elongated if the terminal moves from one location to another during a call. In this dissertation, the problem of allocating backbone links among the ATM switches to reduce the effects of terminal mobility on network performance is investigated. A simple efficient algorithm is proposed to address this problem. The proposed algorithm is comprised of two schemes, namely, fixed window scheme and variable window scheme, both of which are based on a common set guidelines to govern the way links are included in the backbone network. Simulation result shows that the assignment of backbone links obtained by our proposed heuristic algorithm is able to keep the average length of the communication path as short as possible which in turn allows more communication paths to be established in this network.